Pemanfaatan Media Pembelajaran IPS Sekolah Dasar di Kecamatan Banyuurip - Bawon Supriyati; Gunawan Sridiyatmiko (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to explain the use of social studies learning media in elementary schools in Banyuurip District with all kinds of school conditions. It is hoped that the characteristics of learning media that can be used and their efforts to improve, as well as efforts to increase teacher creativity in making learning media, can be known. This type of research is descriptive qualitative, because this study describes the phenomenon of learning that is in schools in Banyuurip District. The research uses social situations, namely places, actors, and activities that interact synergistically. Data were collected through observation, interviews and documentation. Sources of data are principals and elementary school teachers in Banyuurip District. The analysis technique uses an interactive model from Miles and Huberman to analyze the research data. Activities in qualitative data analysis are carried out interactively and take place continuously until complete. The data validity technique uses data triangulation. The results showed: (1) the media problems found in Elementary Schools in Banyuurip District include incomplete media according to social studies lessons, special media storage space is not available so that many media are damaged, lost and not maintained, the media needed are not all available so that teachers find it difficult, teachers find it difficult to make and use media due to limited insight in their use, (2) the use of media in elementary schools is not maximized, due to school limitations. In general, the use of media is carried out by teachers in Banyuurip District in using mass media or groups in front of the class. Some teachers have used social studies learning media such as globes, maps, atlas books, and focused LCDs.